Effectiveness of The Implementation of The Independent Curriculum In Man 2, Cilegon City, Banten Province - Rosidah Rosidah; Nana Suryapermana; Mochamad Subekhan; Paiman Paiman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the effectiveness of the implementation of the Independent Curriculum (IKM) at State Islamic Senior High School (MAN) 2 in Cilegon City, which was designated as the “Piloting Project” for IKM in Banten Province by the Directorate General of Islamic Education, Ministry of Religious Affairs of the Republic of Indonesia. The study used a descriptive qualitative approach, collecting data through documentation, observation, and interviews. Primary data were obtained from interviews with informants, while secondary data came from the Independent Curriculum documents and related literature. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that the implementation of IKM at MAN 2 Cilegon City has been effective. The implementation strategy includes leadership commitment, optimizing stakeholder roles, and institutional partnerships. The managerial stages include planning with socialization and appointment of project-based learning coordinators (P5 and P2RA), integrated implementation of intracurricular and project-based learning, and monitoring and evaluation through internal and office meetings. This implementation has successfully instilled the values ​​of Pancasila and religious moderation, demonstrated the effectiveness of the Merdeka Curriculum in building student character, creativity, and skills, and served as an example of successful innovative curriculum management practices.